"PROMETEU": MITH AND REALITY AT THE UNIVERSITY (Fiep Bulletin - online, 2014)
Abstract: This paper of theoretical investigation aims at integration the myth horizon to the university universe in order to shake its image of producing knowledge engagement, manifested on the investigation of reality, making it closer to the university day-to-day. It also wants to approach the theme of University under mythology perspective, verifying the following belief: what labels the myth of University, engaged with reality, is not the equality; in fact, what labels this myth is the difference, the divergence on the convergence, the multiple facing the unity. This makes the university.
Keywords: University; myth; Prometeu